2009
DOI: 10.1093/sleep/32.6.737
|View full text |Cite
|
Sign up to set email alerts
|

Long Working Hours and Sleep Disturbances: The Whitehall II Prospective Cohort Study

Abstract: Working long hours appears to be a risk factor for the development of shortened sleeping hours and difficulty falling asleep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
197
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(214 citation statements)
references
References 39 publications
15
197
0
2
Order By: Relevance
“…Previous studies investigating the impact of long working hours on health used time standards for normal working hours and long working hours that differed from those used in this study. A cohort study conducted in the UK defined long working hours as working 55−60 hours a week, and studies in Japan defined long working hours as working more than 55 hours or working 61 hours or more 6,9,18) . Another study defined long working hours as working 45 hours or more a week 27) .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigating the impact of long working hours on health used time standards for normal working hours and long working hours that differed from those used in this study. A cohort study conducted in the UK defined long working hours as working 55−60 hours a week, and studies in Japan defined long working hours as working more than 55 hours or working 61 hours or more 6,9,18) . Another study defined long working hours as working 45 hours or more a week 27) .…”
Section: Discussionmentioning
confidence: 99%
“…Shortened sleep due to long working hours or overtime may thus increase the likelihood of insufficient recovery from fatigue (9-11) and stressrelated diseases (12)(13)(14)(15). Therefore, an intervention to ensure adequate sleep is required to protect workers' health and well-being.…”
mentioning
confidence: 99%
“…A cohort study conducted in the UK reported that the OR for short sleep duration (<7 hours) was 3.24 (95% CI: 1.45−7.27) among subjects working >55 hours per week when those with 35−40 working hours per week were used as a reference 9) . In addition, large-scale cross-sectional studies conducted in Australia 10) and the USA 14) indicated that short sleep duration was associated with working long hours.…”
Section: Discussionmentioning
confidence: 99%
“…In November 2010, Kobayashi et al conducted a systematic review of studies published in 1998 or later on the role played by sleep duration in the association between working hours and cerebrovascular/cardiovascular diseases 8) . They found only two reports on the association between working hours and sleep duration (a cohort study in the UK 9) and a large-scale crosssectional study in Australia 10) ) and recommended further studies on this issue 8) .…”
mentioning
confidence: 99%